Risk of GoTo Company's Big Data Monopoly Reviewed from the Anti-Monopoly Law - Valencia Gustin; Helza Nova Lita; Aam Suryamah (International Journal Labs, 2022)
Background: The convergence of the digital era due to the influence of globalization developments brings awareness of economic value to data for business purposes. Business activities carried out in the digital era tend to use data as material for market research studies, including in determining company policies in the future. As two companies engaged in the digital market, Gojek and Tokopedia have great control over the variety of data of their consumers so that mastery of data is the dominant factor in both. Objective: This study aims to discuss how legal arrangements in Indonesia regarding the practice of data monopoly as a form of unhealthy business competition and whether merger activities between Gojek and Tokopedia that can cause potential data monopolies can be justified according to Law Number 5 of 1999 concerning Monopoly and Business Competition Well. Methods: This research is a normative research conducted by focusing on the study of primary, secondary, and tertiary um huk materials. Results: The results of the study show that at this time there is no strict supervision and limitation of data control from the GoTo company and is still included in the gray realm to be concluded as a monopoly act according to Law Number 5 of 1999. Conslusion: In Indonesia, the practice of data monopoly is currently still regulated by referring to Law No. 5 of 1999 concerning the Prohibition of Monopoly Practices and Unfair Business Competition. According to these provisions, the monopoly occurs and is prohibited when control of the data can then cause unfair business competition in the market, the existence of price controls, and prevent other business actors from entering and competing in the market. As a result, the mastery of Big Data brings business actors to have full dominance in the market. If this is proven to happen, then according to the provisions in the laws and regulations, business actors can be threatened with criminal sanctions of fines and imprisonment in accordance with the losses they have caused